2015
DOI: 10.12697/jeful.2015.6.3.04
|View full text |Cite
|
Sign up to set email alerts
|

Emfaas ja fookus eesti keeles

Abstract: Artiklis tutvustatakse uurimust, mille eesmärk on selgitada välja lauselõpulist kitsast fookust laiast fookusest eristava emfaatilise primaarse lauserõhu akustilised korrelaadid eesti keeles. Tähenduseristust kandvat emfaasi vaadeldakse ka lause eelviimasel sõnal, kus selle realiseerumist ei mõjuta prosoodilise piiri korrelaadid. Uurimus täiendab varasemat uurimust, milles testiti emfaasi korrelaate piirieelses positsioonis. Uurimuse tulemusena leitakse, et piirieelses positsioonis ebaoluliseks osutunud põhito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…Additionally, the average pitch contour of mida -SQs shown in Figure 5 (middle panel) suggests that the wh-phrase of mida -SQs can receive an emphatic pre-nuclear accent. SQs also contained more upstepped accents, which can likewise be associated with emphasis in Estonian (Sahkai, Mihkla & Kalvik 2015). All these prosodic characteristics convey the emotional expressivity of SQs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, the average pitch contour of mida -SQs shown in Figure 5 (middle panel) suggests that the wh-phrase of mida -SQs can receive an emphatic pre-nuclear accent. SQs also contained more upstepped accents, which can likewise be associated with emphasis in Estonian (Sahkai, Mihkla & Kalvik 2015). All these prosodic characteristics convey the emotional expressivity of SQs.…”
Section: Discussionmentioning
confidence: 98%
“…Upstepped pitch accents are usually associated with emphasis marking, e.g. to signal narrow focus as opposed to broad focus (Sahkai, Mihkla & Kalvik 2015). An upstepped nuclear ^H*þL is characteristic of polar questions (Asu 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The Estonian quantity system comprises three quantity degrees realised through a binary length distinction at segmental level in combination with three distinct duration ratios of stressed and unstressed syllables at foot level, e.g., ude [uteˑ] 'down', uude [uːte] 'innovation', uude [uːːtĕ] 'new.ill.sg' (for an overview see Metslang et al 2023: 74-81;Asu et al 2016;Lippus et al 2013;Prillop 2013;Lehiste 1960). On the phrasal level, duration is employed in preboundary lengthening (Plüschke & Harrington 2013;Krull 1997), as the primary dynamic correlate of phrasal stress (Lehiste 1968(Lehiste , 1970Mihkla & Sahkai 2017), and as the primary correlate of emphatic phrasal stress distinguishing narrow focus from broad focus (Suomi et al 2013;Mihkla et al 2015;Sahkai et al 2015). Measurements have shown that both pre-boundary lengthening (Plüschke & Harrington 2013) and lengthening as a correlate of non-emphatic (Lehiste 1968(Lehiste , 1970 and emphatic (Sahkai et al 2015) phrasal stress apply in a way that preserves the characteristic foot-level duration ratios of the three quantity degrees.…”
Section: Cross-linguistic Correlates Of Word Stressmentioning
confidence: 99%
“…Artiklis vaatlesin konverbitarindit kirjakeeles, kus infostruktuur avaldub eeskätt sõnajärjes. Et infostruktuuril on olulised foneetilised korrelaadid (Sahkai, Mihkla & Kalvik 2015, Mihkla & Sahkai 2017, väärivad edaspidi uurimist suulise keele konverbitarindid. Samuti puudutas artikkel mitut teemat, mis väärivad lähemat uurimist: konverbitarindi inforolli seos tarindi sisemise infostruktuuriga, süntaktilise ja semantilise funktsiooni seos inforolliga ning infostruktuuri seos verbi asukoha ja kirjavahemärgistusega.…”
Section: Kokkuvõteunclassified